On the tolerance averaging of heat conduction for periodic hexagonal-type composites = Uśrednianie tolerancyjne przewodnictwa ciepła w kompozytach o periodycznej strukturze heksagonalnej - Wierzbicki, Ewaryst (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper deals periodic composites which two-dimensional material structure is determined by the anisotropic conductivity matrix invariant with respect to the pair of translations such that the periodic cell determined by them coincide with the shapely hexagon.
Keywords: tolerancyjne uśrednianie; kompozyt; przewodnictwo cieplne; tolerance averaging; periodicity cell; shapely hexagon; orthogonalization method